Escolha de genitores e desempenho agronômico de híbridos de milho - Silva, Paulo Roberto da (2012)
Corn crop is essential for Brazilian agriculture, due to economic and social importance for the country. Grain yield has been increasing gradually over the years, in part due to genetic gain from selection. The objectives of this work were to evaluate the behavior of some agronomic traits in parents and their single-cross hybrids and reciprocals, and the relationship of these characters with grain yield and plant density; and to study the performance of corn hybrids in high yield environments based upon the analysis of phenotypic adaptability and stability. The first part of the work was conducted in an experimental field in Cruz Alta/RS, during 2010/2011 growing season. Five inbred parents and eight hybrids synthesized from the inbred lines were evaluated. The experiments were carried out in a factorial (genotype x densities x planting dates) in a randomized complete block design with four replications. The evaluations were: plant height, leaf area index, ear index, thousand grain weight, number of grains per ear and grain yield. Heterosis was obtained from the parent s average. In the second part of the work, 48 environments were used to evaluate the grain yield from ten maize hybrids. The hybrid s behavior was studied according to the average yield in poor and/or high-quality environments, the parameters estimates of the discontinuous bi-segmented equation, and the equation adjustment. The plant density was an important management practice to maximize the maize hybrids yield and heterosis estimates showed that the inbreeds have a higher tolerance to increased plant density. The yield potential of hybrids was influenced by the specific combining ability and reciprocal effect was observed for the traits plant height, leaf area index, grain weight, number of grains per ear and grain yield. The reciprocal effect was randomly controlled, sometimes by male or female parent, thus there was not a standard behavior for all traits. If there is no reciprocal effect, we can choose the female parent with higher seeds yield for a particular cross, otherwise, the parent needs to be chosen according to the best specific combination. There was a really good phenotypic stability in single-cross hybrids, with high yield potential. Adaptability and stability characteristics are intrinsic from each hybrid combination.